2018
DOI: 10.1111/ijfs.14038
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic regulation of the extent of dietary proteins with skin grape proanthocyanidin and anthocyanidin's interactions

Abstract: During technological processing, proanthocyanidins and anthocyanidins could be partly lost due to the complexation phenomena, affecting food and beverage nutritional properties, organoleptic properties and health-promoting potentials. A common issue is encountered when processing food and beverage which is binding of phenolics to dietary proteins. The present investigation aims at evaluating the proteolysis contribution, using pure protease (Pepsin, 3000 units g À1 ), to protein-anthocyanidin and protein-proan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The extraction procedure has to be as cautious as possible. Several studies highlighted the proper utilization of acetone to separate high molecular weight phenolics, especially tannins (Ben Abdallah et al., 2018). Using this method, data obtained showed that total polyphenol content of the pomegranate and persimmon skin purified extract was, respectively, 82.49 ± 3.21 and 19.92 ± 0.96 mg GAE/g DW starting material (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The extraction procedure has to be as cautious as possible. Several studies highlighted the proper utilization of acetone to separate high molecular weight phenolics, especially tannins (Ben Abdallah et al., 2018). Using this method, data obtained showed that total polyphenol content of the pomegranate and persimmon skin purified extract was, respectively, 82.49 ± 3.21 and 19.92 ± 0.96 mg GAE/g DW starting material (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…This was not the case in our finding; but, in contrast, obtained results (Table 1) illustrated a decrease of absorbance at 280 nm, therefore, deduced as a decrease of proanthocyanidins. Additionally, we excluded in a previous work (Ben Abdallah et al., 2018) the hypothesis of any matching protein significant detection, given that the entirety tyrosine and tryptophan percentage content of casein did not exceed 6.3%. This level is judged insufficient to support eventual contributing role those two aromatic amino acids to the recorded absorbance at 280 nm wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations